Thin, soft, 3D printing enabled crosstalk minimized triboelectric nanogenerator arrays for tactile sensing - Li, Jian; Liu, Yiming; Wu, Mengge; Yao, Kuanming; Gao, Zhan; Gao, Yuyu; Huang, Xingcan; Wong, Tsz Hung; Zhou, Jingkun; Li, Dengfeng; Li, Hu; Li, Jiyu; et al. (Fundamental research (Beijing), 2023)
With the requirements of self-powering sensors in flexible electronics, wearable triboelectric nanogenerators (TENGs) have attracted great attention due to their advantages of excellent electrical outputs and low-cost processing routes. The crosstalk effect between adjacent sensing units in TENGs significantly limits the pixel density of sensor arrays. Here, we present a skin-integrated, flexible TENG sensor array with 100 sensing units in an overall size of 7.5 cm × 7.5 cm that can be processed in a simple, low-cost, and scalable way enabled by 3D printing. All the sensing units show good sensitivity of 0.11 V/kPa with a wide range of pressure detection from 10 to 65 kPa, which allows to accurately distinguish various tactile formats from gentle touching (as low as 2 kPa) to hard pressuring. The 3D printing patterned substrate allows to cast triboelectric layers of polydimethylsiloxane in an independent sensing manner for each unit, which greatly suppresses the cross talk arising from adjacent sensing units, where the maximum crosstalk output is only 10.8%. The excellent uniformity and reproducibility of the sensor array offer precise pressure mapping for complicated pattern loadings, which demonstrates its potential in tactile sensing and human-machine interfaces. [Display omitted]